A lignocellulolytic enzyme system for fruit waste degradation : commercial enzyme mixture synergy and bioreactor design - Gama, Repson (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Studies into sources of alternative liquid transport fuel energy have identified agro-industrial wastes, which are lignocellulosic in nature, as a potential feedstock for biofuel production against the background of depleting nonrenewable fossil fuels. In South Africa, large quantities of apple and other fruit wastes, called pomace, are generated from fruit and juice industries. Apple pomace is a rich source of cellulose, pectin and hemicellulose, making it a potential target for utilisation as a lignocellulosic feedstock for biofuel and biorefinery chemical production. Lignocellulosic biomass is recalcitrant in nature and therefore its degradation requires the synergistic action of a number of enzymes such as cellulases, hemicellulases, pectinases and ligninases. Commercial enzyme cocktails, containing some of these enzymes, are available and can be used for apple pomace degradation. In this study, the degradation of apple pomace using commercial enzyme cocktails was investigated. The main focus was the optimisation of the release of sugar monomers that could potentially be used for biofuel and biorefinery chemical production. There is no or little information reported in literature on the enzymatic degradation of fruit waste using commercial enzyme mixtures. This study first focused on the characterisation of the substrate (apple pomace) and the commercial enzyme cocktails. Apple pomace was found to contain mainly glucose, galacturonic acid, arabinose, galactose, lignin and low amounts of xylose and fructose. Three commercial enzyme cocktails were initially selected: Biocip Membrane, Viscozyme L (from Aspergillus aculeatus) and Celluclast 1.5L (a Trichoderma reesei ATCC 26921 cellulase preparation). The selection of the enzymes was based on activities declared by the manufacturers, cost and local availability. The enzymes were screened based on their synergistic cooperation in the degradation of apple pomace and the main enzymes present in each cocktail. Viscozyme L and Celluclast 1.5L, in a 50:50 ratio, resulted in the best degree of synergy (1.6) compared to any other combination. The enzyme ratios were determined on Viscozyme L and Celluclast 1.5L based on the protein ratio. Enzyme activity was determined as glucose equivalents using the dinitrosalicylic acid (DNS) method. Sugar monomers were determined using Megazyme assay kits. There is limited information available on the enzymes present in the commercial enzyme cocktails. Therefore, the main enzymes present in Viscozyme L and Celluclast 1.5L were identified using different substrates, each targeted for a specific enzyme and activity. Characterisation of the enzyme mixtures revealed a large number of enzymes required for apple pomace degradation and these included cellulases, pectinases, xylanases, arabinases and mannanases in different proportions. Viscozyme L contained mainly pectinases and hemicellulases, while Celluclast 1.5L displayed largely cellulase and xylanase activity, hence the high degree of synergy reported. The temperature optimum was 50ÂºC for both enzyme mixtures and pH optima were observed at pH 5.0 and pH 3.0 for Viscozyme L and Celluclast 1.5L, respectively. At 37ÂºC and pH 5.0, the enzymes retained more that 90% activity after 15 days of incubation, allowing the enzymes to be used together with less energy input. The enzymes were further characterised by determining the effect of various compounds, such as alcohols, sugars, phenolic compounds and metal ions at various concentrations on the activity of the enzymes during apple pomace hydrolysis. Apart from lignin, which had almost no effect on enzyme activity, all the compounds caused inhibition of the enzymes to varying degrees. The most inhibitory compounds were some organic acids and metal ions, as well as cellobiose and xylobiose. Using the best ratio for Viscozyme L and Celluclast 1.5L (50:50) for the hydrolysis of apple pomace, it was observed that synergy was highest at the initial stages of hydrolysis and decreased over time, though the sugar concentration increased. The type of synergy for optimal apple pomace hydrolysis was found to be simultaneous. There was no synergy observed between Viscozyme L and Celluclast 1.5L with ligninases - laccase, lignin peroxidase and manganese peroxidase. Hydrolysing apple pomace with ligninases prior to addition of Viscozyme L and Celluclast 1.5L did not improve degradation of the substrate. Immobilisation of the enzyme mixtures on different supports was performed with the aim of increasing stability and enabling reuse of the enzymes. Immobilisation methods were selected based on the chemical properties of the supports, availability, cost and applicability on heterogeneous and insoluble substrate like apple pomace. These methods included crosslinked enzyme aggregates (CLEAs), immobilisation on various supports such as nylon mesh, nylon beads, sodium alginate beads, chitin and silica gel beads. The immobilisation strategies were unsuccessful, mainly due to the low percentage of immobilisation of the enzyme on the matrix and loss of activity of the immobilised enzyme. Free enzymes were therefore used for the remainder of the study. Hydrolysis conditions for apple pomace degradation were optimised using different temperatures and buffer systems in 1 L volumes mixed with compressed air. Hydrolysis at room temperature, using an unbuffered system, gave a better performance as compared to a buffered system. Reactors operated in batch mode performed better (4.2 g/L (75% yield) glucose and 16.8 g/L (75%) reducing sugar) than fed-batch reactors (3.2 g/L (66%) glucose and 14.6 g/L (72.7% yield) reducing sugar) over 100 h using Viscozyme L and Celluclast 1.5L. Supplementation of Î²- glucosidase activity in Viscozyme L and Celluclast 1.5L with Novozyme 188 resulted in a doubling of the amount of glucose released. The main products released from apple pomace hydrolysis were galacturonic acid, glucose and arabinose and low amounts of galactose and xylose. These products are potential raw materials for biofuel and biorefinery chemical production. An artificial neural network (ANN) model was successfully developed and used for predicting the optimum conditions for apple pomace hydrolysis using Celluclast 1.5L, Viscozyme L and Novozyme 188. Four main conditions that affect apple pomace hydrolysis were selected, namely temperature, initial pH, enzyme loading and substrate loading, which were taken as inputs. The glucose and reducing sugars released as a result of each treatment and their combinations were taken as outputs for 1"“100 h. An ANN with 20, 20 and 6 neurons in the first, second and third hidden layers, respectively, was constructed. The performance and predictive ability of the ANN was good, with a RÂ² of 0.99 and a small mean square error (MSE). New data was successfully predicted and simulated. Optimal hydrolysis conditions predicted by ANN for apple pomace hydrolysis were at 30% substrate (wet w/v) and an enzyme loading of 0.5 mg/g and 0.2 mg/mL of substrate for glucose and reducing sugar, respectively, giving sugar concentrations of 6.5 mg/mL and 28.9 mg/mL for glucose and reducing sugar, respectively. ANN showed that enzyme and substrate loadings were the most important factors for the hydrolysis of apple pomace.
Keywords: Enzymes -- Biotechnology; Enzymes -- Industrial applications; Lignocellulose -- Biodegradation; Biomass energy; Biomass conversion; Biochemical engineering; Agricultural wastes as fuel